PENINGKATAN KUALITAS PEMBELAJARAN BERBASIS KONTRUKTIVISME MELALUI MEDIA SOSIAL - M. Wahid Nasrudin (Jurnal Teladan: Jurnal Ilmu Pendidikan dan Pembelajaran, 2019)
Constructivism theory is the most effective learning, in accordance with the 2013 curriculum which requires students to be more active and creative in developing knowledge coupled with the advancement of technology. This article will review the basics of constructivism, implications outside the classroom and in the classroom, and the use of social media as an improvement in the quality of learning. Besides that, the dilemma in using social media with various problems is also mentioned. The purpose of using the media as an improvement in the quality of learning is that students are better able to use smartphones as possible.